2017
DOI: 10.1504/ijise.2017.10002583
|View full text |Cite
|
Sign up to set email alerts
|

Management and operations maintenance for a water treatment and supply company

Abstract: This paper intends to highlight the importance of the maintenance activity for all kind of companies in general and for the water treatment companies in particular. To attain this objective a literature review on the evolution of the maintenance concept, the relation between the production function and the Total Productive Maintenance (TPM) and the factors that influence the success of TPM is performed. To demonstrate the contribution of the maintenance activity for the improvement of the performance of compan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Nevertheless, Makropoulos and Butler fail to mention some of the technological solutions that can be adopted by the water sector [8]. Matias et al found that productive maintenance has a positive correlation with an improvement in water provision [9]. However, this publication does not mention how this approach can address the gap in the water supply to the ever-growing global population.…”
Section: Problem Overview and Scope Of Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, Makropoulos and Butler fail to mention some of the technological solutions that can be adopted by the water sector [8]. Matias et al found that productive maintenance has a positive correlation with an improvement in water provision [9]. However, this publication does not mention how this approach can address the gap in the water supply to the ever-growing global population.…”
Section: Problem Overview and Scope Of Workmentioning
confidence: 99%
“…Management and operations maintenance for a water treatment and supply company Journal article Matias et al, 2015 [9] It highlights that the introduction of total productive maintenance in the water industry can help improve company performance with regards to the provision of water services.…”
Section: Type Of Document Authors and Date Findingsmentioning
confidence: 99%
See 1 more Smart Citation